ECOPATTERN MANGROVE: EKSPLORASI TEKNIK BATIK LUKIS DAN PEWARNA ALAM PADA MODEST WEAR - Salwa putri Lingga; Suharno; Mira Marlianti (Universitas Negeri Surabaya, 2026)
The creation of the Ecopattern Mangrove collection aims to offer innovative modest wear that takes ecological aspects into account. This is based on the significant market demand for environmentally friendly modest fashion and the still limited references for creating modest wear that combine mangrove motifs with natural dyes and painted batik techniques. Therefore, the novelty of this creation is the exploratory synergy between painted batik techniques with natural dyes tingi and jolawe on rayon and cotton fabric materials, resulting in a visual character in the form of an organic texture, earthy nuances, and a distinctive natural color effect. The creation method used is the Three Stage Design Process which consists of three stages: Problem Definition and Research, Creative Exploration, and Implementation. Through this method, four modest wear looks are produced with the application of environmentally friendly materials as an identity of sustainable luxury. The implications of this creation for science are providing alternative developments in textile design and sustainable fashion, especially in the realm of modest wear.